Cost-sharing mechanism design for ride-sharing. (August 2021) - Hu, Shichun; Dessouky, Maged M.; Uhan, Nelson A.; Vayanos, Phebe
Abstract: In this paper, we focus on the cost-sharing problem for ride-sharing: determining how to allocate the total ride cost between the driver and the passengers. In particular, we focus on the scenario where drivers are also commuters with the goal of cost recovery. We identify the properties that a desirable cost-sharing mechanism should have and develop a general framework that can be used to create specific cost-sharing mechanisms. We propose specific mechanisms and analyze their relative advantages and disadvantages so that service providers can select a mechanism according to their different needs. In addition, we incorporate the value of time by allowing passengers to have inconvenience costs due to extra travel time caused by detours for picking up the passengers, and provide discount methods to compensate for these costs. We evaluate our approach using real traffic data from the downtown Los Angeles area. Our results show that each proposed mechanism has its unique advantages and that the discount methods can successfully reduce the number of no-passenger vehicles for a large ride-sharing system. Highlights: A ride-sharing mechanism framework for an online system is proposed. Specific mechanisms under the framework are developed and analyzed. Inconvenience costs are taking into consideration and corresponding discount methods are proposed. Simulations on both small and large datasets demonstrate the different benefits one can have by adapting different mechanisms.